Large Scale Identification of Osteosarcoma Pathogenic Genes by Multiple Extreme Learning Machine - Zhao, Zhipeng; Shi, Jijun; Zhao, Guang; Gao, Yanjun; Jiang, Zhigang; Yuan, Fusheng (Frontiers in Cell and Developmental Biology, 2021)
At present, the main treatment methods of osteosarcoma are chemotherapy and surgery. Its 5-year survival rate has not been significantly improved in the past decades. Osteosarcoma has extremely complex multigenomic heterogeneity and lacks universally applicable signal blocking targets. Osteosarcoma is often found in adolescents or children under the age of 20, so it is very important to explore its genetic pathogenic factors. We used known osteosarcoma-related genes and computer algorithms to find more osteosarcoma pathogenic genes, laying the foundation for the treatment of osteosarcoma immune microenvironment-related treatments, so as to carry out further explorations on these genes. It is a traditional method to identify osteosarcoma related genes by collecting clinical samples, measuring gene expressions by RNA-seq technology and comparing differentially expressed gene. The high cost and time consumption make it difficult to carry out research on a large scale. In this paper, we developed a novel method ‘RELM’ which fuses multiple extreme learning ma-chines(ELM) to identify osteosarcoma pathogenic genes. The AUC and AUPR of RELM are 0.91 and 0.88 respectively in 10-cross validation, which illustrates the reliability of RELM.